Improving the electrical resistivity of blast-furnace coke - Koval, Valentine; Miroshnichenko, Denis Viktorovich; Soloviov, Yevhen (Національний технічний університет "Харківський політехнічний інститут", 2025)
The study examines the impact of petroleum coke on coal charges and blast furnace coke quality. Four charge variants with different coal concentrate and petroleum coke contents were analyzed. Adding 5% petroleum coke increased coke structure orderliness and nanostructures while boosting gross coke output by 1.3-1.4%. However, it raised sulfur content (0.12-0.14%) and reduced ash content (0.3-0.4%), while slightly worsening mechanical properties, reactivity, structural strength, abrasive hardness, and electrical resistance. The use of "Svyato-Varvarynska" coal improved coke quality, whereas its lower share in the charge led to a significant decline.
Keywords: coal charges; blast furnace coke; concentrates; petroleum coke; electrical resistivity; quality indicators